Mesocarnivores interactions in fragmented landscapes - Linck, Paloma (2021)
In Iberian Peninsula, large carnivores suffered a significant decline in their populations. Mesocarnivores are therefore one of the main groups of terrestrial predators present in Iberian ecosystems. Mesocarnivore community are extremely complex and presents multidimensional interactions that act on distinct ecological axes. Understanding the factors that determine the organisation of this community is fundamental for an adequate planning and management of conservation actions. My dissertation aimed to evaluate the temporal patterns of mesocarnivore species in response to socio-environmental variables at the Iberian level and assess the influence of landscape heterogeneity on the co-occurrence of species in time and space. At the Iberian level, we compiled camera trap data from eight study areas, collecting a total of 3,719 independent records for the five species studied (red fox, Vulpes vulpes; European badger, Meles meles; stone marten, Martes foina; Egyptian mongoose, Herpestes ichneumon and common genet, Genetta genetta). The analysis revealed that the activity patterns of the species were predominantly influenced by seasonality, with all species studied showing significant differences in their activity between summer and autumn. The red fox, in turn, was characterized by a greater difference in activity between summer and winter, while in summer the species is predominantly nocturnal, in winter its activity became cathemeral. At regional level, in the central-north of Portugal, we sampled 279 points, between June 2019 and June 2020, with camera traps and obtained 1,939 independent records for the five species. The results suggested the influence of several topographic, anthropogenic and environmental variables on each species occupancy. The results also indicated a positive influence of landscape heterogeneity on the spatiotemporal co-occurrence of mesocarnivore species. In temporal co-occurrence, seven of ten species pairs showed greater overlap of their activities in heterogeneous landscapes. When analysing the spatial component, co-occurrence between species pairs was also significantly higher in regions with greater landscape heterogeneity. While in homogeneous landscapes 29% of pairs showed aggregation behaviour, this value increases up to 43% in heterogeneous landscapes. The results emphasize the importance of landscape management towards the maintenance of its heterogeneity, since this characteristic acts positively on the co-occurrence of mesocarnivore species. In the current context of ecosystem degradation, there is a widespread trend towards the habitat simplification, which may have negative repercussions on the dynamics and conservation of Iberian mesocarnivore communities.